2019
DOI: 10.1186/s42234-019-0025-z
|View full text |Cite
|
Sign up to set email alerts
|

Identification of hypoglycemia-specific neural signals by decoding murine vagus nerve activity

Abstract: Background: Glucose is a crucial energy source. In humans, it is the primary sugar for high energy demanding cells in brain, muscle and peripheral neurons. Deviations of blood glucose levels from normal levels for an extended period of time is dangerous or even fatal, so regulation of blood glucose levels is a biological imperative. The vagus nerve, comprised of sensory and motor fibres, provides a major anatomical substrate for regulating metabolism. While prior studies have implicated the vagus nerve in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 47 publications
(55 reference statements)
3
33
1
Order By: Relevance
“…The firing rate of clusters decreased after administration of glucose, which may suggest that the signaling for glucose intake was met. This observation aligns with previous studies that showed neural recordings from dissected fibers of afferent hepatic vagus nerve branches in isolated and perfused livers using wire electrodes 50 , and compound neural activity from the cervical vagus nerve using cuff electrodes after removing the nerve sheath 35 . Both studies demonstrated similar firing rate changes following the administration of glucose.…”
Section: Discussionsupporting
confidence: 92%
“…The firing rate of clusters decreased after administration of glucose, which may suggest that the signaling for glucose intake was met. This observation aligns with previous studies that showed neural recordings from dissected fibers of afferent hepatic vagus nerve branches in isolated and perfused livers using wire electrodes 50 , and compound neural activity from the cervical vagus nerve using cuff electrodes after removing the nerve sheath 35 . Both studies demonstrated similar firing rate changes following the administration of glucose.…”
Section: Discussionsupporting
confidence: 92%
“…The CFMA was also able to determine the propagation of some of these signals in the afferent direction at a conduction velocity for unmyelinated C-fibers, which dominate the vagus nerve 27,28 . The increase in firing rate observed after insulin or 2-deoxy-D-glucose (2-DG) injection, which induce similar symptoms, may represent a surge of afferent activity to enhance the request for glucose intake, which aligns with the previously mentioned studies that also showed increased afferent activity in the hepatic branch of vagus nerves using wire electrodes 50 , and increased compound activity of cervical vagus nerves using cuff electrodes 35 within 10 minutes after administration of insulin or 2-DG. Similarly, the CFMA detected the afferent propagation of some of these signals at a C-fiber conduction velocity.…”
Section: Discussionsupporting
confidence: 82%
“…Although electrical stimulation-evoked responses can be useful in determining the type of activated fibers, these responses do not represent physiological neural signaling. A few research groups have obtained physiological neural recordings from autonomic nerves using extraneural cuff electrodes [31][32][33][34][35] . However, extraneural electrodes lack spatial selectivity, as these electrodes record the compound activity of hundreds to thousands of axons from outside the nerve.…”
Section: Introductionmentioning
confidence: 99%
“…Recording of electrical vagus nerve activity has revealed that intraperitoneal injection of pro-inflammatory cytokines TNF and IL-1, respectively, results in distinct electrical signatures (Caravaca et al 2017a;Steinberg et al 2016b;Zanos et al 2018;Masi et al 2019). Additionally, motor cortex activity was recorded, decoded, and used to purposefully move a paralyzed patient's own hand by connecting electrodes to muscles in the arm (Bouton et al 2016).…”
Section: Future Perspectives Of Experimental Bioelectronic Medicinementioning
confidence: 99%